2019
DOI: 10.1002/jmri.26729
|View full text |Cite
|
Sign up to set email alerts
|

Monoexponential, Biexponential, and stretched‐exponential models using diffusion‐weighted imaging: A quantitative differentiation of breast lesions at 3.0T

Abstract: Background Diffusion‐weighted imaging (DWI) plays an important role in the differentiation of malignant and benign breast lesions. Purpose To investigate the utility of various diffusion parameters obtained from monoexponential, biexponential, and stretched‐exponential DWI models in the differential diagnosis of breast lesions. Study Type Prospective. Population Sixty‐one patients (age range: 25–68 years old; mean age: 46 years old) with 31 malignant lesions, 42 benign lesions, and 28 normal breast tissues dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
(63 reference statements)
2
15
2
Order By: Relevance
“…Axial 3D fat-saturated T1WI were obtained immediately before contrast administration and at six consecutive time points following the administration of the Gd-DTPA contrast agent, with the following parameters: TR/TE, 5.1/2.1 msec; flip angle, 10; field of view, 320 × 320 mm 2 ; matrix, 400 × 70; and slice thickness, 2.4 mm. ADC maps were generated with a monoexponential fit for the diffusion data with b values of 50 and 800 sec/mm 2 using the following formula: ADC = [lnS0 − lnS( b )]/ b (where S0 and S( b ) represent the DWI signal intensity at b = 50 and 800 sec/mm 2 , respectively [ 20 , 21 ]). EPI (fat-suppressed single-shot spin-echo echo-planar imaging) was used for fat suppression.…”
Section: Methodsmentioning
confidence: 99%
“…Axial 3D fat-saturated T1WI were obtained immediately before contrast administration and at six consecutive time points following the administration of the Gd-DTPA contrast agent, with the following parameters: TR/TE, 5.1/2.1 msec; flip angle, 10; field of view, 320 × 320 mm 2 ; matrix, 400 × 70; and slice thickness, 2.4 mm. ADC maps were generated with a monoexponential fit for the diffusion data with b values of 50 and 800 sec/mm 2 using the following formula: ADC = [lnS0 − lnS( b )]/ b (where S0 and S( b ) represent the DWI signal intensity at b = 50 and 800 sec/mm 2 , respectively [ 20 , 21 ]). EPI (fat-suppressed single-shot spin-echo echo-planar imaging) was used for fat suppression.…”
Section: Methodsmentioning
confidence: 99%
“…The DDC and α values of SEM in our study were also significantly lower in TZ cancer than in SH tissue, which corresponded to previous studies. 15,16 In the SEM, DDC and α were used to evaluate the water diffusion characteristics. Distributed diffusion coefficient can be regarded as a weighted sum of the ADC distribution, representing the mean intravoxel diffusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic performance of IVIM-DWIderived parameters in the differentiation of breast tumors is not consistent, and the application of this sequence remains debatable. For example, several studies (7,11,12) indicated that breast cancer had a higher D * value than did benign lesions, while other studies reported adverse (10,(13)(14)(15) or non-significant results (9,16,17). The studies of Cho et al (9) and Lin et al (13) suggested that the IVIM model can further distinguish invasive ductal carcinoma (IDC) from ductal carcinoma in situ (DCIS), while another study reported no significant difference in the D, D * , and f values between them (7).…”
Section: Introductionmentioning
confidence: 99%